New Technologies and Human Rights : challenges to regulation/ edited by Mario Viola De Azevedo Cunha...[et al] - Cuna, Mario Viola De Azevedo (ed.) (Surrey, 2013)
Whilst advances in biotechnology and information technology have undoubtedly resulted in better quality of life for mankind, they can also bring about global problems. The legal response to the challenges caused by the rapid progress of technological change has been slow and the question of how international human rights should be protected and promoted with respect to science and technology remains unexplored. The contributors to this book explore the political discourse and power relations of technological growth and human rights issues between the Global South and the Global North and uncover the different perspectives of both regions. They investigate the conflict between technology and human rights and the perpetuation of inequality and subjection of the South to the North. With emerging economies such as Brazil playing a major role in trade, investment and financial law, the book examines how human rights are affected in Southern countries and identifies significant challenges to reform in the areas of international law and policy.
Keywords: Human rights